Metagenomic data on the composition of bacterial communities in lake environment sediments for fish farming by next generation Illumina sequencing - Custodio Villanueva, María (2020)
This article contains data on the bacterial communities of lagoon sediments with fish potential in the Central Andes of Peru. The surface sediment samples were collected from four lagoons destined for continental water fish farming. DNA extraction was performed from 0.5 g of sample through the Presto(TM) Soil DNA Extraction Kit. Bacterial sequencing of the 16S rRNA amplicon was performed on the DNA extracted from the sediment. At least 36 Phyla bacteria were detected, the bacterial communities being dominated by Proteobacteria, Cyanobacteria, Actinobacteria, Firmicutes, Chloroflexi. These data can be used for predictive analysis to gain a better understanding of the dynamics of bacterial communities in environments under pressure from fish farming. (C) 2020 The Author(s). Published by Elsevier Inc.